2013
DOI: 10.1590/1414-431x20132856
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ozone oxidative preconditioning in preventing early radiation-induced lung injury in rats

Abstract: Ionizing radiation causes its biological effects mainly through oxidative damage induced by reactive oxygen species. Previous studies showed that ozone oxidative preconditioning attenuated pathophysiological events mediated by reactive oxygen species. As inhalation of ozone induces lung injury, the aim of this study was to examine whether ozone oxidative preconditioning potentiates or attenuates the effects of irradiation on the lung. Rats were subjected to total body irradiation, with or without treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Despite limited redox defenses, mitochondrial dysfunction and apoptosis were limited after irradiation. This might be due to an adaptive response protecting TICAE-ROSI cells against an overflow of ROS, as was observed in other cells (Belikova et al, 2009) and animals (Bakkal et al, 2013). Therefore, we conclude that rosiglitazone improved mitochondrial function in our model and protects against irradiation-induced apoptosis.…”
Section: Discussionsupporting
confidence: 76%
“…Despite limited redox defenses, mitochondrial dysfunction and apoptosis were limited after irradiation. This might be due to an adaptive response protecting TICAE-ROSI cells against an overflow of ROS, as was observed in other cells (Belikova et al, 2009) and animals (Bakkal et al, 2013). Therefore, we conclude that rosiglitazone improved mitochondrial function in our model and protects against irradiation-induced apoptosis.…”
Section: Discussionsupporting
confidence: 76%
“…The dose of ozone (0.7 mg/kg/d i.p) used in the present study has been previously shown to produce OOP in rat skeletal muscle and intestinal tissues [43,44]. In a recent experimental study, Bakkal et al [14] reported that i.p application of ozone at a dose of 0.7 mg/kg/ d for five consecutive days resulted in amelioration of radiation-induced lung injury via reduction of lipid peroxidation and increment of antioxidant superoxide dismutase activity. Based on this knowledge, we preferred to use a similar regimen to constitute experimental OOP and we observed that it exerts its beneficial effects without causing detectable toxicity.…”
Section: Discussionmentioning
confidence: 69%
“…Ozone therapy can induce tolerance to ischemic insults and attenuate ischemiaereperfusion (I/R) injury in various tissues including the kidney [11e13]. This phenomenon is known as ozone oxidative preconditioning (OOP) and has been proposed to protect the organs against oxidative stress [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that intraperitoneally administered ozone decreased the TNF-α level and increased the SOD level in a rat model of experimental peritonitis (4). Bakkal et al repeatedly administered low doses of intraperitoneal ozone to rats with experimentally induced radiation lung injury, and reported a decrease in TNF-α and IL-1β levels, an increase in SOD activity, and a reduction in lung damage (28).…”
Section: Tab 2 Mean Mwm Pft On Days 1-4mentioning
confidence: 99%